Living labs for people in Kenya: Outcomes of participatory action research in Nandi County - Reyes, Byron; Camilo, Karen (2024)
The Low Emission Food Systems Initiative (also known as Mitigate+) focused on three main aspects: reducing food systems (FS) emissions and the predicted consequences of climate change on future generations, sustainable development, and social equity. Through its work, the initiative ensured that civil society, multilateral, government, academic, and private sector actors in its four targeted countries (Colombia, Kenya, China, Viet-Nam) have the knowledge, information, and tools necessary to make robust evidence-based decisions as they confront challenges in FS discourse, policy development, and implementation to reduce greenhouse gas emissions (GHGE) contributions. The initiative aimed to promote inclusive approaches for low-emission FS transformation using a framework denominated Living Labs for People (LL4P). This report focuses on the results of a process evaluation conducted on the LL4P approach, in Kenya. For this, key informants data and secondary data were used. The evaluation allowed us to identify the outcomes that have been achieved as a result of the Initiative, and highlighted that these align perfectly with the conceptualization of a LL4P, as one of the main outcomes was the establishment of the LL4P as a framework that is inclusive, appropriated (co-owned) by stakeholders, and autonomous. Further, the LL4P is fully operational in an autonomous way; it has a board that is inclusive towards gender and youth, and representative of the diverse set of stakeholders in the county; and in 2024, it was able to launch a call for innovations and identify six innovations to receive funding for scaling. The Initiative has contributed by facilitating a space for stakeholders to identify and scale new innovations, using funding that is managed by the LL4P.